2017
DOI: 10.1021/acsnano.7b02533
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Membrane Camouflaged Cascade Bioreactor for Cancer Targeted Starvation and Photodynamic Therapy

Abstract: Selectively cuting off the nutrient supply and the metabolism pathways of cancer cells would be a promising approach to improve the efficiency of cancer treatment. Here, a cancer targeted cascade bioreactor (designated as mCGP) was constructed for synergistic starvation and photodynamic therapy (PDT) by embedding glucose oxidase (GOx) and catalase in the cancer cell membrane-camouflaged porphyrin metal-organic framework (MOF) of PCN-224 (PCN stands for porous coordination network). Due to biomimetic surface fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
450
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 711 publications
(454 citation statements)
references
References 96 publications
3
450
0
1
Order By: Relevance
“…A number of studies have reported the successful use of phototherapy, such as PTT and photodynamic therapy (PDT), in the treatment of cancers [41][42][43][44][45][46] . In our study, PTT only moderately delayed the tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported the successful use of phototherapy, such as PTT and photodynamic therapy (PDT), in the treatment of cancers [41][42][43][44][45][46] . In our study, PTT only moderately delayed the tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…[44,45] Because of these combined observations,m any nano-platforms for PDT have been designed to contain catalase to transform endogenous H 2 O 2 to O 2 . [46][47][48] In 2015, Chen et al constructed aH 2 O 2 -responsive and O 2 -evolving nanocomposite for use in highly selective PDT to overcome tumor hypoxia. [46] In this nanocomposite,c atalase and the PS,m ethylene blue,w ere co-encapsulated into the aqueous core,a nd the quencher,B HQ-3 was doped into the polymeric shell that also contained the cancer cell-targeting group,c (RGDfK).…”
Section: In Situ O 2 Generationmentioning
confidence: 99%
“…Overall, as compared to traditional PSs this innovative nano-PS system enables more efficient and precise PDT against hypoxic tumors.Z hangsg roup also developed two other catalase-containing, cell membrane-coated nanoplatforms for O 2 -elevating PDT. [47,48] In addition to catalase,s everal other nanomaterials,s uch as MnO 2 nanoparticles,g old nanoclusters,p latinum nanozymes,a nd mesoporous cerium oxide hollow nanoparticles, have been used in PDT-related systems to catalyze the transformation of H 2 O 2 to O 2 . [49][50][51][52][53][54][55] Fore xample,L in et al recently fabricated ac atalase-like nanocomposite containing MnO 2 and chlorin e6 by using human serum albumin as the building block.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thus, the efficiency of PDT could be dramatically improved (Phua et al, ). Zhang's group developed cell‐like biomimetic nanoplatform for O 2 self‐sufficient PDT (Cheng et al, ; Li et al, ). Glucose oxidase and catalase were loaded by PS nanoparticles, and then covered by cancer cell membrane.…”
Section: O2 Introduction Carriers Used In Pdtmentioning
confidence: 99%
“…The cascade bioreactor could decompose endogenous H 2 O 2 and intracellular glucose, which not only improved the hypoxia of tumors, but also induced cancer starvation. The synergistic effects of starvation therapy and PDT could effectively inhibit the tumor growth (Li, Cheng, et al, ). Liu's group also designed several catalase conjugated PSs to increase the O 2 concentration of tumors to increase PDT efficiency (Chen et al, ; Meng et al, ; Wang et al, ).…”
Section: O2 Introduction Carriers Used In Pdtmentioning
confidence: 99%